Probiotic and Biotherapeutic Properties of Tannase Positive Lactobacillus plantarum ÌÒÑÑ 6 Strain - I. B. Oriabinska; D. B. Prasanna; L. M. Lazarenko (Антибиотики и Химиотерапия)
The article presents the data on the probiotic properties of Lactobacillus ðlantarum ÌÒÑÑ 2621 strain obtained from the collection of microorganisms and the gene bank of the Institute of Microbial Technologies of India. The distinctive feature of the strain is its ability to produce tannase enzyme, which is connected with the antioxidant properties of the probiotic. It was shown that L.ðlantarum ÌÒÑÑ 2621 is antagonistic to Gram-positive and Gram-negative bacteria, as well as yeast. Its high potential for adhesion (IAM — 7.10±0.39) and selective resistance to a wide range of antibiotics (oxacillin, benzylpenicillin, gentamicin, kanamycin, enrofloxacin, polymyxin C and polymyxin M) were established. The immunological tolerance of the strain as well as its ability to stimulate nonspecific antiviral defense and innate immune system of the organism due to the activation of the synthesis of type I interferon were revealed in series of preclinical studies. The method of spectral-dynamic analysis shows the potential antitumor activity of L.ðlantarum ÌÒÑÑ 2621 against such oncological diseases as squamous and keratinized cervical cancer, uterine myoma, and cystic process.